Design Policy Recommendations and Innovation - Endang Sri Purwanti; Ariyadi. F Ariyadi. F; Susanto Susanto (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This article discusses the importance of developing strategic solutions, designing policy recommendations, and developing innovations in response to increasingly complex global challenges. The background explains the need for proactive, data-driven strategies and policies, complemented by innovation, to ensure their relevance to current developments. The purpose of this paper is to provide a conceptual and practical overview of strategy formulation, policy design, and the role of innovation in their implementation. The writing method uses a literature review, examining strategic management theory, public policy, and examples of innovation in Indonesia. The discussion demonstrates that innovation is key to strengthening the effectiveness of strategies and policies. Case studies of the Merdeka Belajar program and deep learning demonstrate how digital innovation and flexible approaches can improve the quality of public policy.